2011
DOI: 10.1603/an11040
|View full text |Cite
|
Sign up to set email alerts
|

Egg-Dumping Behavior is Not Correlated with Wider Host Acceptance in the Seed Beetle Callosobruchus maculatus (Coleoptera: Chrysomelidae: Bruchinae)

Abstract: If typical host plants are absent, some herbivorous insects "dump" eggs on unsuitable substrates, even though this can cause complete larval mortality and reduced maternal life span. In the seed beetle Callosobruchus maculatus (F. ) (Coleóptera: Chrysomelidae: Bruchinae), the tendency to dump eggs varies genetically both within and between populations. A previous study hypothesized that egg-dumping behavior facilitates host-range expansions, and suggested that such expansions have served to maintain "dumper" g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The earlier initiation and shorter duration of oviposition associated with increased temperature variation may represent the "egg-dumping" behavior of female EAB. Such "egg-dumping" behavior has also been observed with other beetles such as Callosobruchus maculates when stressed with abnormal conditions such as host-deprivation and/or food-shortages (e.g., Messina & Fox, 2011;Messina, Morrey, & Mendenhall, 2007). In addition, our study showed that both O. agrili survival and parasitism rate generally exhibited a negative response to climate variation as well as host densities.…”
Section: Discussionsupporting
confidence: 83%
“…The earlier initiation and shorter duration of oviposition associated with increased temperature variation may represent the "egg-dumping" behavior of female EAB. Such "egg-dumping" behavior has also been observed with other beetles such as Callosobruchus maculates when stressed with abnormal conditions such as host-deprivation and/or food-shortages (e.g., Messina & Fox, 2011;Messina, Morrey, & Mendenhall, 2007). In addition, our study showed that both O. agrili survival and parasitism rate generally exhibited a negative response to climate variation as well as host densities.…”
Section: Discussionsupporting
confidence: 83%
“…The two populations used in this study differed in both their geographic origin and long-term host afÞl-iation, and were known to differ in several ecologically relevant traits (Messina and Slade 1997, Savalli et al 2000, Fox et al 2004a, Messina et al 2007, Messina and Fox 2011. Available molecular data suggest that C. maculatus populations in Africa, where the insect is native, are generally genetically distant to those in various regions of Asia (Berg and Mitchell 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although completely interfertile, the African and Asian strains show strong genetic differences in body size, lifespan, egg-laying behavior, larval competitiveness, degree of male-male competition, paternal investment, and other traits (Messina and Slade 1997, Savalli et al 2000, Messina et al 2007, Messina and Fox 2011. By virtue of differences in larval size and competitive behavior within seeds, the two populations even differ in their impact on seed germination and the subsequent survival of host seedlings (Fox et al 2010).…”
mentioning
confidence: 99%